2017
DOI: 10.1002/ange.201707880
|View full text |Cite
|
Sign up to set email alerts
|

Tree‐Bark‐Shaped N‐Doped Porous Carbon Anode for Hydrazine Fuel Cells

Abstract: Metal-free N-doped porous carbon has great potential as ac atalyst for hydrazine oxidation in direct hydrazine fuel cells (DHFCs). However,p revious studies have reported only half-cell characterization, and the effect of the pore sizedistribution has not been intensively investigated. Herein, we report the synthesis of highly active,m etal-free Ndoped carbon (NDC) by controlling the pore sizedistribution, and for the first time,the effect of the pore size distribution on the anode performance in aDHFC is inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Because the carbon support also showed an activity for the HDOR at this region, the activity of straight-line shape region would be from the carbon. A previous study, which has reported the activities of metal-free carbon materials used for HDOR, supports our suggestion that the straight-line shape region is an irrelevance to Ni properties, because the onset potential for the HDOR on metal-free carbon in LSV is consistent with that observed in our straight-line shape region [30] . Consequently, the 45 wt% Ni/C catalyst shows the best HDOR activity among the as-prepared catalysts.…”
Section: Resultssupporting
confidence: 92%
“…Because the carbon support also showed an activity for the HDOR at this region, the activity of straight-line shape region would be from the carbon. A previous study, which has reported the activities of metal-free carbon materials used for HDOR, supports our suggestion that the straight-line shape region is an irrelevance to Ni properties, because the onset potential for the HDOR on metal-free carbon in LSV is consistent with that observed in our straight-line shape region [30] . Consequently, the 45 wt% Ni/C catalyst shows the best HDOR activity among the as-prepared catalysts.…”
Section: Resultssupporting
confidence: 92%
“…This potential represents a lower overpotential for the HzOR, as compared to previous metal-free carbons at the same pH range, reported to be 0.4-0.6 V vs RHE at pH 14. 27,28 The HzOR efficiency of doped carbon catalysts derived from alkaline earth metal-based precursors is linked with their superior microstructure. 12,28 In contrast, carbons pyrolyzed at lower temperatures performed worse, with lower onset potentials (as positive as 0.79 V vs RHE for C-500) and lower current densities.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 The HzOR efficiency of doped carbon catalysts derived from alkaline earth metal-based precursors is linked with their superior microstructure. 12,28 In contrast, carbons pyrolyzed at lower temperatures performed worse, with lower onset potentials (as positive as 0.79 V vs RHE for C-500) and lower current densities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation